6t-3=6t-3

Simple and best practice solution for 6t-3=6t-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6t-3=6t-3 equation:



6t-3=6t-3
We move all terms to the left:
6t-3-(6t-3)=0
We get rid of parentheses
6t-6t+3-3=0
We add all the numbers together, and all the variables
=0
t=0/1
t=0

See similar equations:

| -10m+2=12-8m | | 2(x+4)-10=3x+6 | | (6x+)+(5x+1)=42 | | f+-7=86 | | .13x+20=25 | | 4x3=-5 | | 2^2+2x+3(2^x)-1=0 | | 89=-4v+57 | | 245-y=124 | | 150m-125m+33425=35,700-150m | | 150m-125m+33425=35,700-150 | | 6x=5+17+2x | | -w+248=114 | | 172=24-v | | 28=-8/9z-4 | | 8x-7+91=180 | | 6+3.58x=25.78 | | 7x=5=11+5x | | 10=v/5-8 | | 6+3.58=25.78x | | 2x=46=7x=6 | | 96.2+1.5x=98.5+0.8x | | 25m-13=62 | | 6x-3.58=25.78 | | 6x+3.58=25.78x | | 30+0.8x=14+1.20x | | 7/2x+1/2x=271/2+9;2x | | 4w-9=3.5w-9 | | 6x+3.58x=25.78 | | -n+94=-7 | | 5/2r=14 | | 19y+31=31 |

Equations solver categories